Effectiveness of Internship Program Results in Students During Pandemic - Delta Apriyani; Henry Ananta; Maharani Kusumaningrum; Sofia Daniati; Sinta Sulis Setyani; Estu Tri Yulia; Ayu Berlyana Sucipto; Marcellina Pangestuti (International Journal of Active Learning, 2023)
Internship is a program that must be implemented for students in university to develop the skills of students and adjust the needed skills in the Business World and the Industrial World in general. In the current pandemic situation there are many obstacles faced by students to implement industry internship activities, one of which is looking for internship places that still give opportunities for students to carry through internships. This pandemic condition also requires students to learn from home both practical learning and theory, so that the possibility for students to experience deficiencies in the abilities or skills used as provisions for internships is still minimal, so it requires the students activity to keep using internship activities as advice to gain knowledge in order to get the maximum learning experience. Through research conducted that with the current pandemic conditions, which require learning to be done online, does not rule out the possibility when internships in students continue to run effectively and provide valuable experiences and help the learning process for students. The assessment conducted by students states that internship activities carried out with the provision of online learning do not reduce the level of effectiveness and spirit for students as evidenced by obtaining an average assessment of the effectiveness of internships which is 4.50 in scale 5 which can be said that online learning does not reduce the level of effectiveness for students in conducting industry internships, In fact, students make the industry internship program as an opportunity to seek as much experience as possible to pursue the shortcomings obtained in the learning process in the classroom.